Temperature variability of Poisson’s ratio and its Influence on the complex modulus determined by dynamic mechanical analysis - Carneiro, Vitor H. (2018)
Dynamic mechanical analysis (DMA) is the usual technology for the thermomechanical viscoelastic characterization of materials. This method monitors the instant values of load and displacement to determine the instant specimen stiffness. Posteriorly, it recurs to those values, the geometric dimensions of the specimen, and Poisson’s ratio to determine the complex modulus. However, during this analysis, it is assumed that Poisson’s ratio is constant, which is not always true, especially in situations where the temperature can change and promote internal modification in the specimens. This study explores the error that is imposed in the results by the determination of the real values of complex moduli due to variable Poisson’s ratios arising from temperature variability using a constant frequency. The results suggest that the evolution of the dynamic mechanical analysis should consider the Poisson’s ratio input as a variable to eliminate this error in future material characterization.